Pengaruh Advertising, Price Perception, Service Quality Dan Celebrity Endorsment Terhadap Keputusan Pembelian Produk Netflix (Studi Kasus Pada Mahasiswa Universitas Islam Malang ) - Zain, Dhanang Taufik; Rizal, Mohammad; Primanto, Alfian Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This research discusses the development of the digital entertainment industry in Indonesia, with a focus on Video on Demand (VOD) and the influence of related factors on the decision to purchase Netflix services among students at the Islamic University of Malang. In recent years, the transformation from traditional entertainment to digital platforms has changed the way people access and enjoy content, especially with the increasing use of the internet and smart devices. This study uses a quantitative approach and explanatory research method to examine the relationship between the variables of Advertising, Price Perception, Service Quality, and Celebrity Endorsement on purchasing decisions. Data were collected through questionnaires distributed to respondents at the Islamic University of Malang. The results showed that these variables have a significant influence on purchasing decisions, where attractive advertisements and positive price perceptions are factors that contribute to the increase in VOD service users. The findings are expected to provide insights for stakeholders in the entertainment industry in formulating marketing strategies that are more effective and relevant to the needs of today's consumers. Keyword : Advertising,Price Perception, Service Quality,Celebrity Endorsment,Purchase Decision